Sirtuins in intervertebral disc degeneration: current understanding - Jianlin Shen; Yujian Lan; Ziyu Ji; Huan Liu (BMC, 2024)
Abstract Background Intervertebral disc degeneration (IVDD) is one of the etiologic factors of degenerative spinal diseases, which can lead to a variety of pathological spinal conditions such as disc herniation, spinal stenosis, and scoliosis. IVDD is a leading cause of lower back pain, the prevalence of which increases with age. Recently, Sirtuins/SIRTs and their related activators have received attention for their activity in the treatment of IVDD. In this paper, a comprehensive systematic review of the literature on the role of SIRTs and their activators on IVDD in recent years is presented. The molecular pathways involved in the regulation of IVDD by SIRTs are summarized, and the effects of SIRTs on senescence, inflammatory responses, oxidative stress, and mitochondrial dysfunction in myeloid cells are discussed with a view to suggesting possible solutions for the current treatment of IVDD. Purpose This paper focuses on the molecular mechanisms by which SIRTs and their activators act on IVDD. Methods A literature search was conducted in Pubmed and Web of Science databases over a 13-year period from 2011 to 2024 for the terms "SIRT", "Sirtuin", "IVDD", "IDD", "IVD", "NP", "Intervertebral disc degeneration", "Intervertebral disc" and "Nucleus pulposus". Results According to the results, SIRTs and a large number of activators showed positive effects against IVDD.SIRTs modulate autophagy, myeloid apoptosis, oxidative stress and extracellular matrix degradation. In addition, they attenuate inflammatory factor-induced disc damage and maintain homeostasis during disc degeneration. Several clinical studies have reported the protective effects of some SIRTs activators (e.g., resveratrol, melatonin, honokiol, and 1,4-dihydropyridine) against IVDD. Conclusion The fact that SIRTs and their activators play a hundred different roles in IVDD helps to better understand their potential to develop further treatments for IVDD. Novelty This review summarizes current information on the mechanisms of action of SIRTs in IVDD and the challenges and limitations of translating their basic research into therapy.